Secure, helpful, lovable. Incorporating user needs in the design of autonomous vehicles systems for public transport. - Dreßler, Annika; Grippenkoven, Jan; Jipp, Meike; Ihme, Klas; Drewitz, Uwe (Trialog Publishers, 2019)
Autonomous, shared, and electric - this is the vision for future transport services that enable both efficient and climate-friendly mobility. The success of such services will crucially depend an their actual use by the population, which is in turn determined by perceptions of their usefulness, ease of use, safety, and attractiveness. The new features even entail some new challenges to users. We present methods to identify user needs and potential use barriers early in the process of designing autonomous vehicles systems for public transport, and give examples from our user-centered research.
Keywords: Verkehr; Öffentlicher Verkehr; Straßenverkehr; Autonomes Fahren; Verkehrsdienstleistung; Verkehrssicherheit; Fahrzeug; Gestaltung; Information; Fahrgast; Verkehrsmittelwahl